Penyuluhan Branding Profesi Apoteker dan Edukasi Terkait Diabetes di SMA Negeri 16 Medan - Salmah Handayani Lubis (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Tjut Nyak Dhien, 2023)
In order to welcome the 53rd Anniversary of the Faculty of Pharmacy, University of North Sumatra and World Pharmacist Day 2022, the professional organization of Pharmacists (IAI) in Medan city and several universities / Health Institutes in Medan city which have Pharmacist study programs are involved in these activities. In connection with this, I as a representative of the Tjut Nyak Dhien University College as well as the IAI Medan City branch manager through the community service and disaster response team participated in holding these activities in several schools, one of which was SMA Negeri 16 Medan. The purpose of this activity is to introduce the pharmacist profession to SMA Negeri 16 students in the form of educational levels to achieve the pharmacist profession, the duties and responsibilities of pharmacists, the work fields of the pharmacist profession, the job prospects of the pharmacist profession in the future and the role of pharmacists in society, one of which is contained in community service activities through counseling activities branding the pharmacist profession and education related to diabetes.